Eksperimen Sederhana Pembinaan Kebahasaan dengan Model Pretest-Posttest untuk Meningkatkan Pemahaman Penulisan Huruf Kapital, Tebal, dan Miring Siswa di Desa Manggungsari - Elsa Purnama Sari; Ifah Afivah; Ira Waridah; Yosri Deasni Putri; Yuni Ertinawati (Universitas Palangka Raya, 2025)
This study aims to enhance primary school students' understanding of the use of capital letters, bold letters, and italic letters through structured language development activities. Employing a quantitative approach with a simple pretest-posttest experimental design, the research was conducted on 12 students in Mangungsari Village, Tasikmalaya Regency, selected based on criteria of active participation and basic writing comprehension. Data were collected using the Quiziz instrument consisting of multiple-choice and simple essay questions, with pretest administered before intervention and posttest afterward. Pretest results showed an average comprehension of 67%, with the greatest weakness in italic letters (53%). After a one-day development session using aids such as PowerPoint and mini infocus, posttest results significantly improved to 92%, with an overall increase of 25%. Specifically, italic letters rose from 53% to 91%, capital letters from 69% to 93%, and bold letters from 78% to 92%. This development successfully reduced comprehension gaps among students and demonstrated the effectiveness of the pretest-posttest model in improving spelling skills, aligning with the Merdeka Curriculum's emphasis on basic literacy.